Cardiotoxicity in platinum-based chemotherapy: Mechanisms, manifestations, and management - Rachma, Betty; Savitri, Merlyna; Sutanto, Henry (Cancer pathogenesis and therapy, 2025)
Platinum-based chemotherapy, a cornerstone in the treatment of various malignancies, is often limited by its potential cardiotoxic effects. Understanding these effects is crucial for optimizing patient outcomes and guiding treatment decisions. This review explores the mechanisms, clinical manifestations, detection, management, and future directions in the research of cardiotoxicity associated with platinum-based chemotherapy. The mechanisms discussed here include oxidative stress, reactive oxygen species production, DNA damage, and alterations in signaling pathways. Clinical manifestations range from mild symptoms to severe complications, including Takotsubo cardiomyopathy, as highlighted by recent case studies. The role of diagnostic tools such as echocardiography, cardiac magnetic resonance imaging, and cardiac biomarkers in early detection is emphasized, underscoring the importance of regular cardiac monitoring. Management strategies focus on cardioprotective agents, alternative chemotherapy regimens, and emerging therapeutic approaches, including the potential of nano liposomal and cubosomal formulations. The review also delves into the future of personalized medicine in predicting and managing cardiotoxicity, advocating for ongoing research to mitigate these adverse effects. This comprehensive overview aims to enhance the understanding of cardiotoxicity in platinum-based chemotherapy, informing clinical practices and promoting patient-centric care. [Display omitted] •Platinum-based chemotherapies cause direct myocardial/DNA damage, oxidative stress, and alterations in signaling pathways.•Clinical manifestations range from asymptomatic changes to severe conditions, including Takotsubo cardiomyopathy.•Advancements in diagnostic tools of echocardiography, cardiac magnetic resonance (CMR), and cardiac biomarkers have improved disease detection.•Management of cardiotoxicity includes the use of cardioprotective agents and alternative chemotherapy regimens.